2012
DOI: 10.1088/0004-637x/749/2/122
|View full text |Cite
|
Sign up to set email alerts
|

SGR J1550–5418 BURSTS DETECTED WITH THEFERMIGAMMA-RAY BURST MONITOR DURING ITS MOST PROLIFIC ACTIVITY

Abstract: We have performed detailed temporal and time-integrated spectral analysis of 286 bursts from SGR J1550−5418 detected with the Fermi Gamma-ray Burst Monitor (GBM) in 2009 January, resulting in the largest uniform sample of temporal and spectral properties of SGR J1550−5418 bursts. We have used the combination of broadband and high time-resolution data provided with GBM to perform statistical studies for the source properties. We determine the durations, emission times, duty cycles, and rise times for all bursts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
119
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(142 citation statements)
references
References 48 publications
(117 reference statements)
22
119
1
Order By: Relevance
“…They are sometimes found in young supernova remnants and are characterized by recurrent emission of short duration, ∼0.1 s (Kouveliotou 1995), bursts of soft gamma-rays/hard X-rays with spectra described by optically thin thermal bremsstrahlung (OTTB) at kT ∼ 20-40 keV (Goǧus et al 2001). Recent studies at lower energies, <15 keV, have found that an OTTB model is no longer accurately fitted to the spectra and there is a rollover which can be best fitted with two blackbodies or alternatively a cutoff power law (Feroci et al 2004;Olive et al 2004;Nakagawa et al 2007;Israel et al 2008;Lin et al 2011;van der Horst et al 2012). There is evidence that these bursts are the result of starquakes that occur when the NS crust fractures due to a buildup of stress associated with the evolution of the strong magnetic field, greater than 10 14 G (Thompson & Duncan 1995).…”
Section: Introductionmentioning
confidence: 99%
“…They are sometimes found in young supernova remnants and are characterized by recurrent emission of short duration, ∼0.1 s (Kouveliotou 1995), bursts of soft gamma-rays/hard X-rays with spectra described by optically thin thermal bremsstrahlung (OTTB) at kT ∼ 20-40 keV (Goǧus et al 2001). Recent studies at lower energies, <15 keV, have found that an OTTB model is no longer accurately fitted to the spectra and there is a rollover which can be best fitted with two blackbodies or alternatively a cutoff power law (Feroci et al 2004;Olive et al 2004;Nakagawa et al 2007;Israel et al 2008;Lin et al 2011;van der Horst et al 2012). There is evidence that these bursts are the result of starquakes that occur when the NS crust fractures due to a buildup of stress associated with the evolution of the strong magnetic field, greater than 10 14 G (Thompson & Duncan 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This activity was observed by several high-energy missions, creating a good opportunity for investigating the broadband spectra of magnetar short bursts and intermediate flares in detail. Broadband spectral properties have been reported by several authors (e.g., van der Horst et al, 2012;Lin et al, 2012;Younes et al, 2014). …”
Section: Introductionmentioning
confidence: 81%
“…In early October 2008, both the Swift Burst Alert Telescope (BAT) and the Fermi Gamma Ray Burst Monitor (GBM) were triggered by numerous bursts from the source SGR 1550-5418 (Israel et al, 2010;von Kienlin et al, 2012). The source entered a second, even more active phase on 22 January 2009, during which a large number of bursts were observed by several satellites, as detected by Swift (Gronwall et al, 2009), Fermi GBM (Connaughton andBriggs, 2009;von Kienlin and Connaughton, 2009), Konus-Wind (Golenetskii et al, 2009), and RHESSI (Bellm et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the peak energy parameter of the Comptonized (often labeled as COMPT) model is interpreted in relation to the electron temperature. Time integrated spectral analysis of nearly 300 bursts from SGR J1550−5418 result in an average power law photon index of −0.92 and peak energy (E peak ) is typically around 40 keV (van der Horst et al 2012). …”
Section: Introductionmentioning
confidence: 99%